1984
DOI: 10.2307/1937769
|View full text |Cite
|
Sign up to set email alerts
|

The Longleaf Pine Islands of the Ocala National Forest, Florida: A Soil Study

Abstract: Longleaf pine—wiregrass—turkey oak (Pinus palustris—Aristida stricta—Quercus laevis) occurs as isolated islands, 60—4000 ha in area, in a matrix of sand pine—scrub (Pinus clausa—Quercus spp.) on deep sands of the Ocala National Forest, Florida. Striking contrasts in physiognomy and species composition, and sharp, stable boundaries suggested that soil differences determined vegetation boundaries. Examination of soils to a 500 cm depth at 130 locations revealed no consistent differences in profile morphology, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Piperno (1985) found that phytoliths did not experience much downward movement in tropical silts and clays and a similar result was reported by Kalisz and Stone (1984) in their studies of phytoliths in porous sands in Florida. However, Hallsworth and Waring (1964) found that phytoliths were washed from the A horizon into the B horizon in sediments in New South Wales indicating that downward movement of phytoliths in sediments is possible (Hallsworth and Waring 1964).…”
Section: Taphonomic Processes Affecting Phytolithssupporting
confidence: 75%
“…Piperno (1985) found that phytoliths did not experience much downward movement in tropical silts and clays and a similar result was reported by Kalisz and Stone (1984) in their studies of phytoliths in porous sands in Florida. However, Hallsworth and Waring (1964) found that phytoliths were washed from the A horizon into the B horizon in sediments in New South Wales indicating that downward movement of phytoliths in sediments is possible (Hallsworth and Waring 1964).…”
Section: Taphonomic Processes Affecting Phytolithssupporting
confidence: 75%
“…The methods used in the phytolith analysis followed those of Kalisz and Stone (1984), Miles and Singleton (1975) and Rovner (1971). Samples were taken within each vegetation type along transects 1, 2, 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…1c) is slowly eroded by rain and wind, as well as disturbance because of tracking of movements of animals over it. Scrub soils are entisols, undeveloped soils with no profile that closely resemble the parent sediment (Kalisz and Stone, 1984). Gopher Tortoise burrowing is a fundamental step in developing these soils, by bringing deeper sediments to the surface, where it is aerated and weathered.…”
Section: Synthesis: Geomorphology and Geometrymentioning
confidence: 99%